1993
DOI: 10.1021/ja00079a024
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic studies of the coupled binuclear non-heme iron active site in the fully reduced hydroxylase component of methane monooxygenase: comparison to deoxy and deoxy-azide hemerythrin

Abstract: A combination of circular dichroism (CD) and magnetic circular dichroism (MCD) spectroscopies has been used to probe the geometric and electronic structure of the binuclear Fe(II) active site of the reduced hydroxylase component of methane monooxygenase (MMOH). Excited-state data provide the numbers and energies of d -* d transitions which are interpreted in terms of ligand field calculations to estimate the geometry of each iron. Variabletemperature variable-field (VTVH) MCD data are analyzed by using a non-K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
130
0
6

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(149 citation statements)
references
References 9 publications
13
130
0
6
Order By: Relevance
“…For example, interactions of regulatory subunits such as MMOB with the hydroxylase protein of methane monooxygenase and acyl carrier protein with Δ 9 -desaturase affect the spectroscopic characteristics of the diiron(II) cluster at the active site. [117][118][119] These observations led to the concept of carboxylate shifts controlling the number of open coordination sites and the range of Fe-Fe distances during catalytic turnover. 120 Thus, in NOR, where glutamate side chains in the vicinity of coordinating histidine residues are known to be conserved, it is conceivable that carboxylate shifts might control the coordination of diatomic molecules at the heme/non-heme diiron site.…”
Section: The Diiron Site Can Accommodate Two Co Moleculesmentioning
confidence: 99%
“…For example, interactions of regulatory subunits such as MMOB with the hydroxylase protein of methane monooxygenase and acyl carrier protein with Δ 9 -desaturase affect the spectroscopic characteristics of the diiron(II) cluster at the active site. [117][118][119] These observations led to the concept of carboxylate shifts controlling the number of open coordination sites and the range of Fe-Fe distances during catalytic turnover. 120 Thus, in NOR, where glutamate side chains in the vicinity of coordinating histidine residues are known to be conserved, it is conceivable that carboxylate shifts might control the coordination of diatomic molecules at the heme/non-heme diiron site.…”
Section: The Diiron Site Can Accommodate Two Co Moleculesmentioning
confidence: 99%
“…The dinuclear iron centers of the hydroxylase reside just 12 Å below the canyon floor, and it has been suggested that the binding sites of MMOR and MMOB may be located in these deep recesses (8). The results of spectroscopic (9,10), chemical crosslinking (11), and steady-state kinetic and isothermal calorimetric (3) studies support this proposal.…”
mentioning
confidence: 96%
“…The soluble MMO (sMMO) is a complex threecomponent system consisting of a hydroxylase, a reductase, and a small regulatory protein (4). The sMMO has been investigated extensively by several research groups (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The xray crystal structure of the sMMO hydroxylase isolated from Methylococcus capsulatus (Bath) has been solved (22,23).…”
mentioning
confidence: 99%